2023
DOI: 10.3389/fitd.2022.1016176
|View full text |Cite
|
Sign up to set email alerts
|

Application of loop mediated isothermal amplification (LAMP) assays for the detection of Onchocerca volvulus, Loa loa and Mansonella perstans in humans and vectors

Abstract: Conventional diagnosis of filarial infections is based on morphological identification of microfilariae using light microscopy and requires considerable expertise, is time-consuming, and can be subjective. Loop-mediated isothermal amplification (LAMP) has advantages over microscopy or PCR because of its operational simplicity, rapidity and versatility of readout options. LAMP assays represent a major step forward in improved filarial diagnostic tools suitable for low resource settings and field applicability. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…Using colorimetric loop-mediated isothermal amplification assay [ 17 ], this study has successfully identified C. grahamii as the potential vector for M. perstans transmission in the middle belt of Ghana. A similar finding was made in the southwest region of Cameroon where C. grahamii was identified as a potential competent vector of M. perstans [ 18 ] even though C. milnei had been identified in earlier studies [ 10 ] to be the main vector in said region. This indicates that C. grahamii is susceptible to M. perstans invasion.…”
Section: Discussionsupporting
confidence: 78%
“…Using colorimetric loop-mediated isothermal amplification assay [ 17 ], this study has successfully identified C. grahamii as the potential vector for M. perstans transmission in the middle belt of Ghana. A similar finding was made in the southwest region of Cameroon where C. grahamii was identified as a potential competent vector of M. perstans [ 18 ] even though C. milnei had been identified in earlier studies [ 10 ] to be the main vector in said region. This indicates that C. grahamii is susceptible to M. perstans invasion.…”
Section: Discussionsupporting
confidence: 78%
“…However, it has been shown that parasitological (skin biopsy) and immunological (OV16 antigen) parameters are in moderate agreement [37]. Therefore, new diagnostics being develop such as multiplex, loop mediated isothermal amplification (LAMP) and others are of interest [38][39][40]. In any acceptability of doxycycline treatment will be much higher in a single round than when skin snip is involved as it is the main determinant of TTd acceptability.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…The UV-light trap collection may be a better method for midge collection than HLC when investigating the prevalence of the infection either by microcopy or molecular assay. Indeed, LAMP was recently used to detect M. perstans , Loa loa and Onchocerca volvulus infections in both engorged and wild-caught Culicoides , Chrysops and Simulium flies, respectively [ 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%